2022
DOI: 10.3390/nu14122374
|View full text |Cite
|
Sign up to set email alerts
|

Increased Omega-3 Fatty Acid Intake Is Associated with Low Grip Strength in Elderly Korean Females

Abstract: Omega-3 fatty acids, such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), have anti-inflammatory properties and have recently been considered essential factors for maintaining muscle health. This study aimed to investigate the relationship between omega-3 fatty acid intakes and sarcopenia by assessing grip strength in elderly Koreans who are at risk of sarcopenia. This study was conducted on 5529 individuals (2449 males and 3080 females) aged ≥65 years from the raw data of the Korea National Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…A noteworthy point of our findings was that intake of EPA, DHA, and fish was associated with the prevalence of LLM and muscle mass in older women, but not in older men. Consistent with the present study, a higher ratio of daily total n-3 PUFA intake to energy intake was negatively associated with the risk of sarcopenic obesity (7), and intake of EPA and DHA was positively associated with handgrip strength (11) in Korean older women, but not in men, suggesting that intake of n-3 PUFA might be beneficial for sarcopenia among Korean women. In the present study, intakes of EPA and DHA, and ALA were analyzed separately instead of n-3 PUFA, and appendicular skeletal muscle mass was evaluated instead of handgrip strength.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A noteworthy point of our findings was that intake of EPA, DHA, and fish was associated with the prevalence of LLM and muscle mass in older women, but not in older men. Consistent with the present study, a higher ratio of daily total n-3 PUFA intake to energy intake was negatively associated with the risk of sarcopenic obesity (7), and intake of EPA and DHA was positively associated with handgrip strength (11) in Korean older women, but not in men, suggesting that intake of n-3 PUFA might be beneficial for sarcopenia among Korean women. In the present study, intakes of EPA and DHA, and ALA were analyzed separately instead of n-3 PUFA, and appendicular skeletal muscle mass was evaluated instead of handgrip strength.…”
Section: Discussionsupporting
confidence: 90%
“…Epidemiologic studies have consistently reported that the intake of total n-3 PUFA, EPA, and DHA was associated with muscle function measured by leg strength, time to rise from a chair, timed up-and-go, gait speed, handgrip strength, and SPPB in American older adults ( 8 ), Japanese men ( 9 ), Finnish women ( 10 ), and Korean women ( 11 ). Similarly, high plasma concentrations of total n-3 PUFA, EPA, and DHA were associated with gait speed, handgrip strength, and SPPB among older adults in a Three-City study ( 13 ) as well as in Korea ( 6 ), United States ( 15 ), and Italy ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation